2001
DOI: 10.1007/bf02256599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a meal feeding schedule on hepatic glycogen synthesis and gluconeogenesis in rats

Abstract: We investigated the effect of a meal feeding schedule (MFS) on food intake, hepatic glycogen synthesis, hepatic capacity to produce glucose and glycemia in rats. The MFS comprised free access to food for a 2-hour period daily at a fixed mealtime (8.00-10.00 a.m.) for 13 days. The control group was composed of rats with free access to food from day 1 to 12, which were then starved for 22 h, refed with a single meal at 8.00-10.00 a.m. and starved again for another 22 h. All experiments were performed at the meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Thus, considering that gluconeogenesis is a metabolic pathway with high energetic cost, it could be suggested that the preference for glycogenolysis could be an adaptation for glycemia maintenance during fasting to overcome the lower food availability (Batista et al, 2001;Bazotte et al, 2000). In conformity with this suggestion, fasting glycemia did not differ (P > 0.05) between CG (97.3±23.3 mg/dL) and RG groups (103.3±25.9 mg/dL).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Thus, considering that gluconeogenesis is a metabolic pathway with high energetic cost, it could be suggested that the preference for glycogenolysis could be an adaptation for glycemia maintenance during fasting to overcome the lower food availability (Batista et al, 2001;Bazotte et al, 2000). In conformity with this suggestion, fasting glycemia did not differ (P > 0.05) between CG (97.3±23.3 mg/dL) and RG groups (103.3±25.9 mg/dL).…”
Section: Resultsmentioning
confidence: 75%
“…Considering that the glucose production before L-Ala infusion resulted from glycogen (Batista et al, 2001), it could be inferred that the livers from RG showed a higher rate of glycogenolysis despite the fact that the hepatic glycogen content was not significantly different between the groups. In contrast, lower (P < 0.05) liver production of glucose and L-lactate during the infusion of L-Ala was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the liver perfusion technique, Batista et al [1] investigated the hepatic glycogen synthesis and gluconeogenesis from alanine and glutamine in meal-fed trained rats. Using the liver perfusion technique, Batista et al [1] investigated the hepatic glycogen synthesis and gluconeogenesis from alanine and glutamine in meal-fed trained rats.…”
Section: Effects Of Meal-fed Training On Rat Hepatic Metabolismmentioning
confidence: 99%
“…Using the liver perfusion technique, Batista et al [1] investigated the hepatic glycogen synthesis and gluconeogenesis from alanine and glutamine in meal-fed trained rats. They showed that meal-fed training increases the activity of hepatic glycogen synthase.…”
Section: Effects Of Meal-fed Training On Rat Hepatic Metabolismmentioning
confidence: 99%